Obesity and its association with aggravation of COVID-19: a systematic review with meta-analysis (Research, Society and Development, 2021)
Objective: To analyze and compile studies linking obesity with complications from COVID-19. Methods: A systematic review with meta-analysis was carried out, using the PECOS strategy: Patient – obese; Exhibition - people with COVID-19; Comparison – not obese; “Outcome” – worsening of the clinical condition; and “Studies” - observational studies. Searches were performed on 06/16/2020 in PubMed, Lilacs and SciELO. Methodological quality was assessed using the STROBE scale and data were qualitatively synthesized. Meta-analysis models were performed for Intensive Care Unit (ICU) need, Invasive Mechanical Ventilation (IMV) and mortality. Results: 24 retrospective studies published in 2020 from different countries were evaluated. The sample size ranged from 53 to 3615 patients, of varying age, of different ethnicities, without gender restrictions and admitted to health centers. In the 8/11 quality assessment, they reached 77% in A or B. Regarding metabolic factors, studies showed that alterations caused by excess adipose tissue favor the deregulation of interleukin levels, triggering a chronic infectious condition. The meta-analysis of the frequency of ICU was 27% among obese, need for IMV was 34% and mortality was 14%. Conclusion: It was found that obesity is a predictor for the worsening of COVID-19. Therefore, obese individuals need an early approach as well as special care in case of contamination.